The role of self-congruity and functional congruity on brand personality-hotel brand loyalty relationship - Hardiana, Shely Rizki (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2023)
Not only testing the direct relationship, but this research also intends to examine the indirect relationship of brand personality (BP) on hotel brand loyalty (BL) through self-congruity (SC) and functional congruity (FC). In addition, functional congruity, a topic that is infrequently researched in the tourism literature, is explored in this study. Using WarpPLS 8.0, this study tests the sample of 227 visitors to a hotel in Yogyakarta. The findings show that brand personality, self-congruity and functional congruity are the antecedents of hotel brand loyalty. This study recommends that hotels strengthen brand personality as an intangible asset to gain loyalty